Pelanggaran Etika Pariwara Indonesia dalam Iklan Reklame Pengobatan Batara di Yogyakarta - Putra, Royan Zanuar; Prasetyo, Rayhan Tri; Fikri, Imam Ikhsanul; Sukmono, Filosa Gita (Universitas Muhammdiyah Yogyakarta, 2025)
This research aims to identify ethical violations in the advertisement of